THE INFLUENCE OF ISLAMIC WORK CULTURE ON EMPLOYEE PRODUCTIVITY WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT THE TENGGARONG PUBLIC SERVICE MALL (MPP) OFFICE - Eva Noorhya Akhmar Ramadhan Putri; Widya Hana Fahleti; Admaja Muhammad Feri (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
This study aims to analyze the effect of Islamic work culture on employee productivity with work discipline as an intervening variable at Mal Pelayanan Publik Tenggarong. The study used a quantitative approach with a survey method. The population consisted of 99 employees, with 92 respondents selected as samples. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3. The results showed that Islamic work culture had a positive and significant effect on employee productivity. Work discipline also had a positive and significant effect on employee productivity. In addition, Islamic work culture had a positive and significant effect on work discipline. Mediation testing indicated that work discipline significantly mediated the effect of Islamic work culture on employee productivity. These findings indicate that the implementation of Islamic values such as trustworthiness, honesty, responsibility, and consistency can improve employee discipline and productivity. Therefore, institutions need to strengthen Islamic work culture and work discipline to improve public service quality and organizational performance sustainably.